If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 1 = 4x + 29 Reorder the terms: 1 + -3x = 4x + 29 Reorder the terms: 1 + -3x = 29 + 4x Solving 1 + -3x = 29 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + -3x + -4x = 29 + 4x + -4x Combine like terms: -3x + -4x = -7x 1 + -7x = 29 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + -7x = 29 + 0 1 + -7x = 29 Add '-1' to each side of the equation. 1 + -1 + -7x = 29 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = 29 + -1 -7x = 29 + -1 Combine like terms: 29 + -1 = 28 -7x = 28 Divide each side by '-7'. x = -4 Simplifying x = -4
| (2/3)x=(-4/7) | | 3/4(2y-8)=16 | | 5*x+4=12*x+3 | | 25-(373/17) | | 15k-10k-4k=14 | | 2(x+2x)=9x-32 | | 3w-2x-y+7w+17x-5y= | | -6(2x-3)=66 | | -14b+15b-(-6)=-6 | | 2(2x+2x)=9x-32 | | -7=-13+6 | | 10q-2q-8q+4q-q=9 | | 12n^3-75n=0 | | -4+3x=-7x+6 | | 6(a+3)=7b | | 3x+1=3x-24 | | Sinx/0,2-2=1,24 | | -2s-8s-(-6s)=8 | | 1.2d-0.5(4d-1)=-0.7(d-2) | | p^2+8p-2=0 | | 9-4x=x-36 | | q-(-11q)-14q+2q-(-2q)=-18 | | 1/8*3= | | 23x+3=25 | | -8-18=x+18 | | 10(p-4)=5c+10 | | 10n-n-(-7n)-7n=-9 | | 8(2n-1)=(5n+8)+1 | | 4+6x+5x=4 | | 16c-12c=4 | | 12-32z=16z+14 | | 3x^2+17x+3=(x+1)(x+13) |